PENGARUH LATIHAN SCALE BAND TERHADAP KELENTURAN OTOT PUNGGUNG SAAT MELAKUKAN SMASH PADA PERMAINAN BOLA VOLLI TIM BOLA VOLLI SMK TARUNA SATRIA PEKANBARU - Tirto, Anggi; ', Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract This study is an experiment.Using experimental and statistical analysis to examining the research done on the sampel. Obtained through an initial test and final test before and after exercise to compare the one groups of sampel with different treatments to fine that practice which is better for Flexsibelity are nice. Due to lack of physical exercise and training programs that are less systematic. The issues raised in this study is "What are the effects of increase exercise Scale Bend the Flexsibelty in those Tim Volly Ball SMK Taruna Satria Pekanbaru" hypothesis in this study was "There Comparative of Exercise Scale Bend the Flexsibelty in those Tim Volly Ball SMK Taruna Satria Pekanbaru ”aims.The analysis showed that there was a significant effect of the increase in exercise Scale Bend (X) and the results of Flexsibelity (Y). Based on the analysis of the results of the t test and the t-count 5.291 and a t-table 2.228. t-calculation> TTable so it can be concluded that H0 is rejected and H1 accepted. Mean increase after tested by t-test showed that t-calculation is greater than t-table, the conclusion exercise for 16 times the Scale Bend drills can improve Flexsibelity and shoulder muscles are significantKeywords: Scale Bend, the Flexsibelity Muscles.